CONCEPTS RELATED TO WATER IN WORLD CULTURES - Kunnazarova Sholpanay Makhsetbaevna (Journal of Learning on History and Social Sciences, 2024)
This article focuses on the concept of water and water-related rituals in world cultures. In it, the concept of water in the worldview of different peoples, their attitude towards it, traditions that have not lost their meaning to this day, are interpreted on the basis of the culture of related or unrelated peoples